Amphiphilic lysine conjugated to tobramycin synergizes legacy antibiotics against wild‐type and multidrug‐resistant Pseudomonas aeruginosa. Issue 1 (16th February 2018) - Lyu, Yinfeng; Domalaon, Ronald; Yang, Xuan; Schweizer, Frank
Abstract: Peptidomimetic modification is a common route of optimization for biologically active peptides. Previous studies in our group have shown that conjugation of amphiphilic tobramycin to other antibacterials enhance their latent outer membrane permeabilizing and efflux blocking activity toward Gram‐negative pathogens including Pseudomonas aeruginosa . Herein, we describe the antimicrobial adjuvant properties of amphiphilic lysine ligated to tobramycin. The most potent amphiphilic lysine‐tobramycin conjugate3 potentiated the antibacterial efficacy of 8 clinically used antibiotics against wild type, multidrug‐ and extensively drug‐resistant P. aeruginosa isolates from Canadian hospitals whereas amphiphilic lysine4 did not. Antibiotics that are synergistic with conjugate3 included moxifloxacin, ciprofloxacin, erythromycin, chloramphenicol, trimethoprim, novobiocin, linezolid, and fosfomycin. Out of these 8 antibiotics, novobiocin showed highest synergy. Abstract :